The impact of combined music and Tai Chi therapy on depressive symptoms among community-dwelling older people in China / Liao Shu Juan - Liao , Shu Juan (2018)
China has more elderly people than any other country in the world, of which nearly one third (27.3%) suffers from subclinical depression in the community setting. The purpose of this study is to determine the prevalence rate of depressive symptoms and its relationship with both quality of life and physical mobility among community-dwelling older people in Ya’an City, China. Furthermore, this study aims to determine the impact of combined music and Tai Chi therapy on depressive symptoms, quality of life, and physical mobility. The study adopted a quantitative design which includes 2 phases. Phase 1 was a cross-sectional survey whereas phase 2 was a single-blinded randomized controlled trial. For phase 1, participants were selected through the cluster systematic randomization method, which resulted in a representative sampling of about 1 in 100 from the district registry, in eight out of sixteen communities in Ya’an City. The sample’s current statuses of depressive symptoms, quality of life, and physical mobility were assessed. Information on the potential risk factors for depressive symptoms and quality of life were collected. Phase 2 used the cluster randomized controlled method to determine the effect(s) of combined music and Tai Chi therapy on depressive symptoms, quality of life, and physical mobility. Two scales were used in this study including the Chinese versions of the Geriatric Depression Scale (GDS) and the World Health Organization Quality of Life BREF (WHOQOL-BREF). The Timed Up and Go (TUG) test was used to assess the physical mobility of older people. The results of this study revealed a 31.3% prevalence rate of depressive symptoms among community-dwelling iv older persons in Southwest China. The average score for the quality of life was 82.44  13.483 and the average time spent to complete the TUG test was 12.11  3.745 seconds. Participants of this study showed a higher prevalence of depressive symptoms and lower levels of quality of life and physical mobility. There was a significant correlation between depressive symptoms, quality of life, and physical mobility, of which the correlation coefficients were -0.657 and 0.511 respectively. Sociodemographic data such as exercise habit, gender, marital status, monthly income, living situation, health problems, and negative life events were found related to depressive symptoms and affected the quality of life. A 50-minute session consisting of 24 Yang’s Tai Chi movements, accompanied by soft and relaxing Chinese folk music that occurs three times a week, lasting three consecutive months, was found effective in reducing depressive symptoms, enhancing the quality of life, and improving the physical mobility of community-dwelling older persons living in Southwest China. The findings of this study would help the nursing profession to gain a better understanding of depressive symptoms in the community context, as well as to recognise the indictors and its relationship with both quality of life and physical mobility. Also, the findings of this study anticipate major implications on the development of achievable and economically viable management of depression among community-dwelling older people in China towards helping the fast-developing, largely-populated, yet aged country to achieve its goal of healthy ageing.